Piezoresistive polymer blends for electromechanical sensor applications - Costa, P. (2018)
Doped polyaniline (PANI) exhibits excellent electrical properties that can be used in composite materials to replace metallic or carbonaceous nanofillers commonly used in composites for sensor applications. Polymer blends based on PANI and thermoplastic elastomer styrene-ethylene/butylene-styrene (SEBS) copolymer have been prepared by solvent casting showing large strain yield (>10% for 40 wt% PANI content), high electrical conductivity, 1 S/m, after the percolation threshold at ≈10 wt% PANI. Further, the composites show suitable piezoresistive response with gauge factor (GF) between GF ≈ 1.5 and 2.4 for deformations up to 10%. The overall properties of the solution casted PANI/SEBS blends indicate their suitability for advanced electromechanical sensors applications, with simple integration and processable by solution printing technologies.